Digital Psychosocial Interventions Tailored for People in Opioid Use Disorder Treatment: Scoping Review - Madison Scialanca; Karen Alexander; Babak Tofighi (Journal of Medical Internet Research)
Abstract BackgroundA total of 60% of patients with opioid use disorder (OUD) leave treatment early. Psychosocial interventions can enhance treatment retention by addressing behavioral and mental health needs related to early treatment discontinuation, but intervention engagement is key. If well-designed, digital platforms can increase the engagement, reach, and accessibility of psychosocial interventions. Prior reviews of OUD treatment have predominantly focused on outcomes, such as reductions in substance use, without identifying the underlying behavior change principles that drive the effectiveness of interventions. ObjectiveThis scoping review aims to document and describe recent digital psychosocial interventions, including their behavior change strategies, for patients receiving medication for OUD (MOUD). MethodsPredefined search terms were used to search Ovid, CINAHL, and PubMed databases for peer-reviewed literature published in the last 10 years. The database search resulted in 1381 relevant studies, and 16 of them remained after applying the inclusion criteria. Studies were included if they (1) evaluated a digital intervention with behavioral, psychosocial, or counseling components for people in OUD treatment and (2) were published in English in peer-reviewed journals. ResultsThe 16 studies reviewed comprised 6 randomized controlled trials, 6 pilot studies, 2 qualitative studies, and 2 retrospective cohort studies. Smartphone apps (n=8) were the most prevalent intervention delivery method, with other studies using telemedicine (n=3), virtual reality (n=1), telephone calls (n=1), or text messaging (n=3) to deliver psychosocial interventions in either a synchronous (n=7) or asynchronous (n=9) manner. The digital interventions reviewed predominately delivered cognitive behavioral therapy education through a phone call (n=1), a text message (n=2), a smartphone app (n=7), or tele-counseling (n=1). The predominant behavior change strategies implemented were self-monitoring, feedback and reinforcement, psychoeducation, cue awareness, and providing instruction. One intervention reviewed uses the evidence base of mindfulness-oriented recovery enhancement. ConclusionsParticipants in the studies reviewed indicated a preference for digital, flexible, patient-centered psychosocial interventions that emphasized improved patient-provider relationships. While randomized controlled trials comprised a significant portion of the studies, the inclusion of pilot studies and qualitative research highlights the field’s ongoing exploration of feasibility and effectiveness. These findings underscore the growing role of digital health solutions in psychosocial care, though further research is needed to optimize engagement, delivery, and long-term outcomes.